Innovative Teaching with TELL: Enhancing Speaking Skills through Digital Applications - Miftahul Jannah; Dhea Nuraisyah; Sumarni Sumarni; Helli Ramdanniah Liswati; Zaitun Qamariah (STIKes Ibnu Sina Ajibarang, 2025)
The ability to speak effectively is an essential component of language proficiency, yet it remains one of the most challenging skills for learners to master. This study investigated the role of Technology Enhanced Language Learning (TELL) tools, such as Duolingo, Zoom, ELSA Speak and YouTube, in improving speaking among language learners. Using desk research, findings show that these tools significantly improve learners' pronunciation, fluency and engagement. For example, Duolingo systematically improves vocabulary and skill development, while ELSA Speak provides real-time pronunciation feedback. Zoom facilitates interactive group discussions through breakout rooms, and YouTube encourages self-directed learning by exposing learners to authentic language content. Despite the benefits, challenges such as limited internet access and suitability of the tools for advanced learners remain. These findings suggest that strategically integrating multiple TELL tools can maximize speaking proficiency outcomes. Future research should explore the long-term impact and cross-context applicability of these tools in language learning.